(untitled) (Scientific Journal of Educational Management, Research and law, 2025)
Artificial intelligence is advancing at incredible speed and becoming part of our everyday lives. This is thanks to the technological advances of the last decades and the spread of digitalization in countless areas. Education is another area where information and communication technologies are an integral part of everyday life. It is therefore inevitable that artificial intelligence is ignored in the field of education. This study examines what AI might imply for education, learning and teaching. Artificial intelligence-based technologies offer a number of benefits for students and teachers alike.